Fusobacterium nucleatum CbpF Mediates Inhibition of T Cell Function Through CEACAM1 Activation - Galaski, Johanna; Shhadeh, Amjad; Umaña, Ariana; Yoo, Christopher C.; Arpinati, Ludovica; Isaacson, Batya; Berhani, Orit; Singer, Bernhard B.; Slade, Daniel J.; Bachrach, Gilad; Mandelboim, Ofer (Frontiers in Cellular and Infection Microbiology, 2021)
F. nucleatum is an anaerobic bacterium that is associated with several tumor entities and promotes tumorigenesis. Recent evidence suggests that F. nucleatum binds the inhibitory receptor carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1) via the trimeric autotransporter adhesin CbpF. However, whether this binding is functional or whether other fusobacterial trimeric autotransporter adhesins are involved in CEACAM1 activation is unknown. In this study, using F. nucleatum mutants lacking the type 5c trimeric autotransporter adhesins fvcA (CbpF), fvcB, fvcC, and fvcD, we show that F. nucleatum CbpF binds and activates CEACAM1 and also binds carcinoembryonic antigen (CEA), a tumor-associated protein. We further find that CEACAM antibodies directed against the CEACAM N-terminal domain block the CbpF-CEACAM1 interaction. In functional assays, we demonstrate CbpF-dependent inhibition of CD4+ T cell response. Thus, we characterize an immune evasion mechanism in which F. nucleatum uses its surface protein CbpF to inhibit T cell function by activating CEACAM1.